2013
DOI: 10.1038/ismej.2013.62
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of loss of the caa3 oxidase and Crp regulation drives Shewanella to thrive in redox-stratified environments

Abstract: Shewanella species are a group of facultative Gram-negative microorganisms with remarkable respiration abilities that allow the use of a diverse array of terminal electron acceptors (EA). Like most bacteria, S. oneidensis possesses multiple terminal oxidases, including two heme-copper oxidases (caa 3 -and cbb 3 -type) and a bd-type quinol oxidase. As aerobic respiration is energetically favored, mechanisms underlying the fact that these microorganisms thrive in redox-stratified environments remain vastly unexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
136
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 74 publications
(154 citation statements)
references
References 46 publications
17
136
1
Order By: Relevance
“…Consistent with our previously reported findings that deletion of Mgfnr affected neither oxygen consumption nor microaerobic magnetite biomineralization in the absence of nitrate (Li et al, submitted), we found that the expression level of the three cbb 3 , aa 3 , and bd terminal oxidase operons was increased by O 2 but not regulated by the global oxygen sensor MgFnr, similar to what was shown previously for Shewanella oneidensis (33). This suggested that some as-yet-unknown O 2 regulators probably mediate the expression of aerobic terminal oxidase genes in response to different oxygen concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our previously reported findings that deletion of Mgfnr affected neither oxygen consumption nor microaerobic magnetite biomineralization in the absence of nitrate (Li et al, submitted), we found that the expression level of the three cbb 3 , aa 3 , and bd terminal oxidase operons was increased by O 2 but not regulated by the global oxygen sensor MgFnr, similar to what was shown previously for Shewanella oneidensis (33). This suggested that some as-yet-unknown O 2 regulators probably mediate the expression of aerobic terminal oxidase genes in response to different oxygen concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…We have previously shown that S. oneidensis prefers insoluble to soluble electron acceptors for respiration, such as Fe (III) oxide versus oxygen, thus preventing endogenous generation of ROS from autoxidation of components of the respiratory chain (35,59). In addition, unlike other organisms containing cytochrome caa 3 -type and cbb 3 -type oxidases, where the low-affinity (caa 3 -type) oxidase plays a dominant role under high-oxygen conditions and the cbb 3 oxidase is induced only at low O 2 concentrations, S. oneidensis utilizes the cbb 3 -type oxidase under both high-and low-oxygen conditions and does not express the caa 3 oxidase (39,40). As respiration of oxygen by the cbb 3 oxidase is relatively slow, less ROS would be generated.…”
Section: Discussionmentioning
confidence: 95%
“…To detect an interaction, vectors containing "bait" (DNA) and "target" (DNA-binding regulator) are cotransformed into BacterioMatch II Validation Reporter competent cells, of which those having positive DNA-protein interactions are able to grow on 3-amino-1,2,4-triazole (3-AT). To calibrate this system, we took advantage of S. oneidensis Crp, which was shown previously to bind to motif sequences upstream of the cyd operon (cytochrome bd oxidase) (55,56). The crp SO gene was cloned into the target vector pTRG, and the cyd promoter containing the Crp SObinding motif was generated by PCR and inserted into the reporter vector pBXcmT.…”
Section: Resultsmentioning
confidence: 99%
“…Although multiple scavenging proteins are encoded in the genome, KatB is apparently the most pivotal one for detoxifying exogenous H 2 O 2 . The dispensability of KatG-2 is likely due to its low expression levels, a scenario similar to the functional loss of cytochrome caa 3 oxidase (56). Given that expression of the katG-1 gene is responsive to H 2 O 2 , why the deletion of the gene fails to elicit any detectable impact remains to be determined.…”
Section: Discussionmentioning
confidence: 99%